Adaptability of Electrospun PVDF Nanofibers in Bone Tissue Engineering - Havlíková, Tereza; Papež, Nikola; Fohlerová, Zdenka; Kaspar, Pavel; Dallaev, Rashid; Častková, Klára; Ţălu, Ştefan (Polymers, 2025)
This study focused on the development of a suitable synthetic polymer scaffold for bone tissue engineering applications within the biomedical field. The investigation centered on electrospun polyvinylidene fluoride (PVDF) nanofibers, examining their intrinsic properties and biocompatibility with the human osteosarcoma cell line Saos-2. The influence of oxygen, argon, or combined plasma treatment on the scaffold's characteristics was explored. A comprehensive design strategy is outlined for the fabrication of a suitable PVDF scaffold, encompassing the optimization of electrospinning parameters with rotating collector and plasma etching conditions to facilitate a subsequent osteoblast cell culture. The proposed methodology involves the fabrication of the PVDF tissue scaffold, followed by a rigorous series of fundamental analyses encompassing the structural integrity, chemical composition, wettability, crystalline phase content, and cell adhesion properties.
Keywords: piezoelectric polymer; polyvinylidene fluoride; scaffold; osteoblasts; bone tissue engineering; electrospinning; bone regeneration; nanofiber fabrication; plasma treatment; cell–substrate interactions; biocompatibility